Diagnosis and Management Practice Patterns among Pediatric Ophthalmology Personnel in Israel. Issue 1 (2nd January 2019) - Barnett-Itzhaki, Guy; Friehmann, Asaf; Barnett-Itzhaki, Zohar; Ela-Dalman, Noa
ABSTRACT: Purpose : To investigate the diagnosis and management practice patterns of different aspects of pediatric ophthalmology among pediatric ophthalmologists and orthoptists in Israel.Methods : A 21-question survey was delivered to all registered pediatric ophthalmologists and orthoptists in Israel.Results : The response rate was 58.3%. Most pediatric ophthalmology personnel in Israel do not document intermittent exotropia (IXT) with a control scale, do not use modalities other than patching for amblyopia, and do not use distance stereoacuity tests. There was no consensus regarding patching and over minus treatments in IXT. In contrast to frequent use of prism adaptation test (PAT) for evaluating strabismus, most Israeli pediatric ophthalmology personnel do not use postoperation diplopia test (PODT). While most orthoptists use a questionnaire when diagnosing convergence insufficiency (CI), most pediatric ophthalmologists do not.Conclusion : This study highlights the current areas of consensus and disagreement regarding pediatric ophthalmology diagnosis and management practices in Israel. Adopting a uniform approach regarding diagnosing CI, including using a questionnaire by pediatric ophthalmologists and orthoptic exercises in the management of IXT, is warranted to enable unified treatment by pediatric ophthalmologist and orthoptists in Israel.